Peran Mediasi Illegitimate Tasks dalam Hubungan Antara Abusive Supervision, Role Conflict dan Organizational Citizenship Behavior - Irlyana Seftya Lindiasari; Gandi Aswaja; Nuri Herachwati (Jayapangus Press, 2026)
Immigration Office, as a public sector organization, faces challenges in meeting increasingly complex demands for public service. One of these challenges is the requirement for employees to possess adaptive capabilities in addressing various task related demands. This study is designed to examine how abusive supervision and role conflict contribute to the decline of organizational citizenship behavior (OCB) through perceptions of illegitimate tasks as a mediating variable. This research employs a quantitative approach using covariance-based SEM analytical techniques. Data were collected through an online questionnaire distributed via Google Forms, consisting on a five point Likert scale. The population consist of all non-structural civil servants across 126 Immigration Offices within two regional offices throughout Indonesia, with a total of 347 respondents obtained as the sample. The sample was selected using purposive sampling based on the criteria of non-structural employees and analyzed using IBM SPSS AMOS. The variables used in this study include abusive supervision (X1) as an independent variable, role conflict (X2) as independent variables, illegitimate tasks (Z) as a mediating variable, and OCB (Y) as a dependent variable. The result indicate that abusive supervision and role conflict have a positive and significant effect on illegitimate tasks. Illegitimate tasks has a negative and significant effect on OCB. Illegitimate tasks also mediates the relationship between abusive supervision, role conflict, and OCB. Practically, the findings of this research may serve as a basis for policymakers at the Immigration Office and other government institution in designing strategies to enhance a healthy, fair, and supportive work climate.